An Investigation of Intercultural Miscommunication Experiences - Sibel Özdemir Çağatay; Ayfer Küllü Sülü (Informascope, 2013)
Communication, which has always been one of the basic elements of life, is becoming more and more intercultural in today's world. People are not only transferring goods and technology among nations; they are also transferring their thoughts, ideas, and cultures. As this flow of communication among nations becomes common, intercultural communication problems, which can be called intercultural miscommunication, is becoming common as well. This paper investigates possible reasons for miscommunication among people from different cultures. Twenty-two participants from different nationalities took part in the study, and shared their intercultural miscommunication experiences. The researchers analyzed these miscommunication experiences by classifying them according to the categories suggested in the literature and the categories the researchers themselves suggested. The participants' feelings and thought about their miscommunication experiences were also investigated. This study showed that there are many causes and factors that can lead to intercultural miscommunication. Thus, effort, desire and patience is needed a lot to get better mutual understanding and learn more about cultural differences so that we can increase cross-cultural awareness.